Description of Self Management of Type 2 Diabetes Mellitus Patients in the Samadua Health Center Working Area, South Aceh Regency - Yenni Sasmita; Fathimi; Desriati Devi; Asmanidar; Asri Jumadewi (Information Technology and Science (ITScience), 2023)
Diabetes mellitus is one of the threats to human health. Diabetes mellitus causes various complications. These complications can be minimized if the patient has the ability and knowledge to manage diabetes (self-management diabetes mellitus). Self-management of diabetes mellitus in this case includes glucose management, dietary control, physical activity, and health care. Objective: to determine the description of self-management in patients with diabetes mellitus in the Samadua Health Center working area, South Aceh Regency. Methods: This research is a quantitative study that uses descriptive methods. The number of samples in this study was 112, using the purposive sampling technique. Data collection instruments were used using the Diabetes Mellitus Management Questionnaire (DMSQ), with a total of 16 question items. Results: The description of self-management of type 2 DM patients in the Samadua Health Center working area is in the good category. Conclusions and Suggestions: The picture of self-management of DM respondents based on the total score of each of the five components is in the good category. More than half of the respondents have a good diet, most have good physical exercise, more respondents do foot care, the majority of respondents have good diabetes medication-taking behavior, and more respondents regularly monitor blood sugar.